Impact of various postharvest wash water conditions on the performance of peracetic acid against Escherichia coli O157:H7 over time. (March 2020) - Ghostlaw, Tiah; Corradini, Maria G.; Autio, Wesley R.; Kinchla, Amanda J.
Abstract: The Produce Safety Rule, part of the Food Safety Modernization Act, mandates zero detectable generic Escherichia coli for certain agriculture wash water applications: hand-washing, food-contact surface washing, or any water which directly contacts produce, including ice. This requirement emphasizes the need to assess and propose mitigation strategies to control E. coli levels in agriculture wash water. As such, this study investigated the relationship between common sanitizers hydrogen peroxide (H2 O2 ) and peracetic acid (PAA) at varying ratios and the influence of concentration, organic load, temperature, and pH on these sanitizers' stability and efficacy against Escherichia coli O157:H7, including re-inoculation to simulate the reintroduction of pathogens during processing. Generally, sanitizers with PAA as the dominant component were more efficient at reducing E. coli O157:H7 levels over time, compared to those with H2 O2 as the dominant component. Of all of the treatments tested, 50/50 H2 O2 /PAA at 80 ppm in the wash water was the most stable over time and had the highest efficacy against E. coli O157:H7 with organic load capacity below 750 mg/l chemical oxygen demand (COD). Organic loads at 750COD were not able to eliminate E. coli after 3.5 h of treatment, compared to all parameters tested. Based on the results of this study, sanitizer composition, concentration, presence of organic load, temperature and pH have the potential to significantly decrease the efficacy and stability of PAA systems over time, indicating that these parameters should be monitored in agriculture wash water utilization to ensure that water quality and safety are maintained. Highlights: Changes in processing water can influence peracetic acid concentration over time. PAA composition over 50%, increased antimicrobial capacity against E. coli O157:H7. PAA concentrations higher than 30 ppm increased antimicrobial capacity over time. 750COD interferes with sanitizer oxidizing capacity and antimicrobial performance.